The first complete mitochondrial genome of Bursidae from Bufonaria rana (Caenogastropoda: Tonnoidea) - Shengping Zhong; Yonghong Liu; Guoqiang Huang; Lianghua Huang (Mitochondrial DNA. Part B. Resources, 2020)
The common frogsnail Bufonaria rana, is an ecologically and economically important Tonnoideans in China due to valuable nutrition and pharmacological compounds. However, the taxonomy and phylogeny of the Bursidae have been debated and synonyms among Bursidae species have been reported recently. In this study, we report the first complete mitochondrial genome of Bursidae from B. rana. The mitogenome has 15,510 base pairs (69.0% A + T content) and made up of total of 37 genes (13 protein-coding, 22 transfer RNAs and 2 ribosomal RNAs), and a putative control region. This study was the first available complete mitogenomes of Bursidae and will provide useful genetic information for future phylogenetic and taxonomic classification of Tonnoideans.